2016
DOI: 10.1111/aej.12175
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intracanal cryotherapy on pain after single-visit root canal treatment

Abstract: The purpose of this study was to evaluate the effect of 2.5°C cold saline irrigation as final irrigant on postoperative pain after single-visit root canal treatment of teeth with vital pulps. One-hundred and seventy patients were assessed as eligible and included to the study. The teeth were randomly divided into two groups (n = 85) (i.e. the control group and the cryotherapy group). In the cryotherapy group, final irrigation with 2.5°C 0.9% physiological saline solution for 5 min was performed following compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
2
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 33 publications
1
69
2
9
Order By: Relevance
“…Two studies so far have used intracanal therapy to evaluate its effect on postoperative pain in patients with both symptomatic and asymptomatic, irreversible pulpitis with either normal apical tissues or symptomatic apical periodontitis. Both studies showed significant lower postoperative pain levels when cryotherapy was applied compared with control groups (24,25). In the present study, only patients presenting uniradicular teeth with a single canal and a diagnosis of necrotic pulp and symptomatic apical periodontitis were included.…”
Section: Discussionmentioning
confidence: 97%
“…Two studies so far have used intracanal therapy to evaluate its effect on postoperative pain in patients with both symptomatic and asymptomatic, irreversible pulpitis with either normal apical tissues or symptomatic apical periodontitis. Both studies showed significant lower postoperative pain levels when cryotherapy was applied compared with control groups (24,25). In the present study, only patients presenting uniradicular teeth with a single canal and a diagnosis of necrotic pulp and symptomatic apical periodontitis were included.…”
Section: Discussionmentioning
confidence: 97%
“…As mentioned earlier, the role played by irrigant solutions on post‐operative pain is inconclusive . However, there are studies which point to a reduction in post‐operative pain by using different strengths and types of irrigating solutions . To the best of the authors’ knowledge, there are no studies evaluating the use of NSAIDs as root canal irrigating solutions and their efficacy in single‐visit root canal treatment for teeth with irreversible pulpitis.…”
Section: Discussionmentioning
confidence: 99%
“…The role of irrigating solutions employed during root canal treatment to help control post‐operative pain is unclear . While certain studies have observed a reduction in post‐operative pain with particular types and concentrations of irrigating solutions, other studies have reported no difference in post‐operative pain with the different irrigating solutions .…”
Section: Introductionmentioning
confidence: 99%
“…These periapical injuries often lead to periapical inflammation known as flare-ups. 1 Several strategies have been developed for postoperative pain management including prescribing prophylactic analgesics and corticosteroids, administering long-lasting anaesthesia, root canal preparation using the crown-down technique and occlusal reduction. 1 Cryotherapy is a long-standing technique that has been frequently applied in sports injuries and surgical procedures for pain management and postoperative care.…”
Section: < 529mentioning
confidence: 99%
“…Türktekin and colleagues (2018) 1 reported on a randomized clinical trial that sought to compare diamond burs and curettes in non-surgical periodontal treatment of chronic periodontitis patients.…”
mentioning
confidence: 99%